2017
DOI: 10.21767/1791-809x.1000503
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Attempted Suicide Patients Presenting to a Greek Emergency Department

Abstract: Background: Attempted suicide is a major health problem internationally and a common cause of presentation to emergency department. The identification of the potential contributing factors associated with suicide attempts is of great importance for effective suicide prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Indeed, our study showed that a personal history of suicide attempt was significantly higher among women compared to men, and this difference was statistically significant. This result confirmed previous findings that suicide attempt rates were higher among women than men in many countries (Filippatos & Karasi, 2017; Lee et al, 2012; Muheim et al, 2013; Narishige et al, 2014; Zhao et al, 2015). In line with these findings, a study has explained the gender difference in suicidal behavior by the fact that women survive suicide attempts more often than men because they use less lethal means (Freeman et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, our study showed that a personal history of suicide attempt was significantly higher among women compared to men, and this difference was statistically significant. This result confirmed previous findings that suicide attempt rates were higher among women than men in many countries (Filippatos & Karasi, 2017; Lee et al, 2012; Muheim et al, 2013; Narishige et al, 2014; Zhao et al, 2015). In line with these findings, a study has explained the gender difference in suicidal behavior by the fact that women survive suicide attempts more often than men because they use less lethal means (Freeman et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, other studies showed that psychotic disorders were associated with jumping from heights, while substancerelated disorders were associated with self-poisoning (Huisman et al, 2010;Persett et al, 2018). Similarly, self-poisoning was the most often used method for suicide attempts in many countries (Filippatos & Karasi, 2017;Lee et al, 2012;Muheim et al, 2013). Therefore, the methods of suicide attempts may vary among countries and depend With regard to risk factors for suicide attempts, our multivariate analysis revealed significant association of female gender, alcohol use, and family history of suicide attempts with suicide attempts among psychiatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the number of attempted suicides in spring and winter was relatively higher than in summer and autumn. This is in line with studies conducted in Europe and Middle East Asia where higher rates of attempted suicide was noted in spring and winter [10][11] . The reason for such seasonal variation is likely due to the biological, cultural and bio-climatic factors 12 .…”
Section: Discussionsupporting
confidence: 92%
“…Campaigns to improve health literacy could reduce “overuse” of emergency services [ 65 ]. Reducing emergency overcrowding could reduce treatment delays, mortality, medical errors, and improve patient satisfaction [ 66 ]. Demographic changes have led to a shift towards older patients and more chronic conditions with an increase in low-acuity and non-urgent cases [ 2 , 17 , 26 ].…”
Section: Discussionmentioning
confidence: 99%